Meniscus of the Knee Function, Pathology and Management - Abdulwahab, Taiceer; Almqvist, Karl (IntechOpen, 2019)
The principal aim of this title is to provide the arthroscopic orthopaedic surgeon with a clear, concise account of the anatomy, pathology, conservative and operative surgical techniques in the management of meniscal pathology. Meniscal lesions are extremely common, and arthroscopic meniscal surgery is one of the most common orthopaedic surgical procedures performed. The art of meniscal surgery involves many steps, with ever-evolving techniques and implants. This book has been prepared during a period of widespread debate on, and evolution in, the conservative, surgical, and biological techniques for managing meniscal lesions. This text will help consolidate the current evidence to enable the development of optimal management plans for meniscal injuries.